Determination of optimal system parameters to characterize the wrinkle recovery of fabrics by an integrated shape retention evaluation system. Issue 1 (January 2020) - Lu, Yuzheng; Hu, Xiaorui; Sun, Fengxin; Peng, Fujian; Gao, Weidong
Measurement methods based on the visual testing principle have been widely used for evaluating the wrinkle recovery property of fabrics; however, the cumbersome testing process and poor adaptability for various fabrics are the main shortcomings of these methods. Here, a facile mechanical testing method named the integrated shape retention evaluation system (ISRES) was developed, providing an alternative approach to assess the wrinkle recovery, as well as the compression recovery and elastic recovery of fabrics. The optimal system parameters of the ISRES in measuring the wrinkle recovery angle were determined using an orthogonal experiment design based on correlation analysis between the curve parameters from the force–displacement curves of the ISRES and the wrinkle recovery angles tested by a standard Shirley crease recovery tester. Moreover, the sensitivity of the ISRES for the differences of the wrinkle recovery of fabrics was analyzed. The results showed that the selected optimal system parameters were a good combination, and the ISRES with the optimal system parameters provided a feasible method to differentiate the wrinkle recovery of fabrics.